Model Lembaga Pendaftaran Nama Domain Dikaitkan Dengan Undang-Undang Nomor 11 Tahun 2008 Menuju Kepastian Hukum - Helni Mutiarsih Jumhur (The Constitutional Court of the Republic of Indonesia, 2016)
The research focuses on the institutional model of the domain name ditemukannhya formed by society but still under the control of government in which the formation of a domain name registration management agency ( registry ) was formed on the recommendation of a domain name forum so that in accordance with the principles contained in that form institutions UUITE domain name come from the government or the public and to ensure legal certainty of the user domain name. The method used is qualitative normative juridical using secondary data in the form of legislation in order to harmonize legislation both vertically and horizontally in order to find out the problems that occur in the establishment of a domain name and is supported by the primary data in the form of in-depth interviews with expertis in the field Information technology. The conclusion derived from this study is a model of the domain name registration body ( registrar ) is formed from the community who have received a license from the agency managing the domain name ( registry ) that has been recommended by the government through forums domain name.